The essence of the legal framework and conditions for the provision of trust services in the european union in the period 2015 – 2030 рр. - Горбенко, Юрій Іванович (Ukrainian Information Security Research Journal, 2013)
The problems of the condition and the need to improve the regulatory and legal legislative base of the European Union (EU) for electronic trust operations in the domestic market are considered. The main provisions of the "Regulations of the European Parliament and the Council for electronic identification and trust services for electronic transactions in the domestic market" are analyzed. The conclusion of the relevance and the need of Ukraine's accession to the electronic digital EU market and related research and development performance are presented. The status of public key infrastructure practice application in European Union and electronic digital signature in Ukraine is analyzed. The basic issues that emerged in the application of electronic digital signature such as unification, standardization, interoperability, scalability, cryptographic stability, complexity of cryptographic transformations are adducted. proposals are developed, and the essence and conditions of the main provisions for the practical implementation of the Regulation, including the future of Ukraine are defined. Requirements that must be addressed in the EU to provide secure electronic services for electronic identification, electronic authentication, electronic signature, electronic seals, electronic time stamps, electronic documents, electronic service delivery and web-site authentication are identified.